Manufacture Indicator Paper for BSL or Small Bungur Extract (Lagerstroemia Indica L) as an Indicators Alternative of Acid-Base - Sri H. V. Pulukadang; Magfira (Jurnal Akademika Kimia, 2022)
This study aims to utilize extracts of local cherry blossoms or small bungur (Lagerstroemia Indica L) in the manufacture of indicator paper as an alternative acid-base indicator. Local Cherry Blossoms were macerated with methanol for ± 2 hours. Extracts and indicator paper of local cherry blossoms were tested as indicators in an acid-base solution, the buffer was then compared with phenolphthalein and methyl orange indicators for acid-base titration, namely strong acid and strong base, weak acid and strong base and weak base and strong acid. The results obtained in this study are: local cherry blossom extract is brownish yellow, in a strong acid it is pink, in a strong base it is dark green, in a weak acid it is pale pink and in a weak base it is light green. The indicator paper of local cherry blossom extract in strong acid is light pink, a strong base is yellow, a weak acid is pale pink, and a weak base is light green. In the buffer, the indicator paper of local cherry blossom extract has a pH range of 4-5 colors (pink-green), and 7-11 colors (yellow-green), the stability of the indicator paper from filter paper can maintain its color for 25 days. The type of acid-base titration that is suitable for the use of local cherry blossom extract indicators, precisely in the titration of strong acid-strong base and the weak acid-strong base is good to use as a substitute for phenolphthalein indicator, while in weak base-strong acid titration it is better to use as a substitute for methyl orange.